PENGARUH KUALITAS AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN PADA PT. TRI SAPTA JAYA CABANG SIBOLGA - Nanda Lestari Tambunan; Yacub Hutabarat; Ramadiah Hanum (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to determine whether or not there is an influence of audit quality on the accuracy of company financial reporting at PT.Tri Sapta Jaya, Sibolga Branch. The hypothesis put forward is that there is an influence of audit quality on the timeliness of PT. Tri Sapta Jaya Sibolga Branch. The author uses 20 respondents as a sample taken from 20 populations using the slove formula. The results of the study indicate that there is a positive relationship between audit quality and timeliness of company financial reporting at PT. Tri Sapta Jaya Sibolga Branch and its correlation coefficient is 0.906, so when interpreted on a value scale it can be categorized as very strong. While the coefficient of determination is known that Audit Quality only plays a role of 82.1%, on the Timeliness of Company Financial Reporting at PT. Tri Sapta Jaya Sibolga Branch and the remaining 17.9% is influenced by other factors not examined. The regression equation obtained Y = 5.750 + 0.925X which shows that if you add one unit of variable X (Audit Quality) or a certain value, it will increase the increase in Variable Y (Timeliness of Reporting) by the regression coefficient of 0.925. Based on the results of the Hypothesis Test which was carried out by comparing the t-count and t-table values, it was found that the t-count value was greater than t-table, namely 9.099 > 2.109 and a significance value of 0.000 below α 5%. Because t count is greater than t table, there is an effect of audit quality on the timeliness of corporate financial reporting at PT. Tri Sapta Jaya Sibolga Branch and the proposed hypothesis was accepted. Keywords: Audit Quality and Timeliness of Reporting